Bond Spreads and Economic Activity in Eight European Economies. (29th February 2016) - Bleaney, Michael; Mizen, Paul; Veleanu, Veronica
Abstract : We provide new insights into the relationship between financial market tightness and real activity, using a new database of corporate bonds issued in eight European countries. Bond spreads have a significant negative relationship with four real activity variables at horizons 1–8 quarters ahead. The relationship is robust to adding measures of monetary policy tightness and leading indicators, providing strong support for models previously only evaluated on US data. A subset of northern European countries have similar sensitivity of real GDP to bond spreads, but others have greater sensitivity to bond spreads, revealing diverse responses in Europe to financial market tightness.